Autoimmune thyroiditis presenting as interstitial granulomatous dermatitis Dermatite intersticial granulomatosa como apresentação de tireoidite autoimune - Joana Antunes; David Pacheco; Ana Rita Travassos; Luís Miguel Soares-Almeida; Paulo Filipe; Manuel Sacramento-Marques (Sociedade Brasileira de Dermatologia, 2012)
A 54-year-old female presented with recurrent, widespread, erythematous, painful plaques, over a 3-month period. Skin biopsy was compatible with interstitial granulomatous dermatitis. Additional investigation revealed hypothyroidism and positive anti-thyroid antibodies. Normalization of thyroid function and high-potency topical corticosteroids provided only transitory improvement of the dermatosis. Interstitial granulomatous dermatitis is a histologic inflammatory reaction, with variable cutaneous expression. It has been reported in association with several drugs, lymphoproliferative diseases and autoimmune disorders, such as rheumatoid arthritis, systemic lupus erythematosus and vasculitis, but association with autoimmune thyroiditis is rare. Optimal therapy for this condition is yet to be established, but topical corticosteroids have been a mainstay of treatment. In most cases, this disease is characterized by flares and remissions. Uma doente de 54 anos foi avaliada por placas eritematosas, dolorosas, disseminadas, recorrentes, com 3 meses de evolução. A biopsia cutânea foi compatível com dermatite intersticial granulomatosa. Os restantes exames laboratoriais revelaram hipotiroidismo e anticorpos anti-tiroideus positivos. Apesar da normalização da função tiroideia e de tratamento com corticóide tópico de alta potência, a dermatose melhorou apenas parcialmente. Dermatite intersticial inflamatória é um diagnóstico histopatológico, com expressão clínica variável. Tem sido associada a vários fármacos, doenças linfoproliferativas e autoimunes, nomeadamente artrite reumatóide, lupus eritematoso sistémico e vasculites, mas a associação com tireoidite autoimune é rara. Até ao momento, não foi definido nenhum tratamento específico, mas os corticóides tópicos são dos fármacos mais utilizados. A doença caracteriza-se por períodos de agravamento e remissão.